The Triumph of Hate : the Political Theology of the Hitler Movement. - Vasillopulos, Christopher (University Press of America, 2011)
The Triumph of Hate explains the religious, philosophical, sociopolitical, and historical roots of the rise of Hitler and his movement. Beginning with Paul's rejection of traditional Judaism, the book accounts for the ani.